Edaphic conditions affect plant life‐history trait syndromes in a tropical ancient biodiverse ecosystem - Gomes, Vanessa M.; Renton, Michael; Riviera, Fiamma; Hobbs, Richard J.; Aguilar, Ramiro; Fernandes, Geraldo Wilson (Austral ecology, 2024)
A functional approach to understand natural plant communities helps elucidate the dynamics of environmental filters and community assembly. Species classification into functional groups allows the translation of ecological complexity into simplified and applicable knowledge. Here, we developed a plant functional type (PFT) system to investigate whether functional structure (PFT composition and abundance) of plant communities varies between substrate types and plant physiognomies in an old climatically buffered infertile landscape (OCBIL), namely Brazilian campo rupestre. We sampled the herbaceous and shrubby vegetation and collected soil variables in four different plant physiognomies growing in quartzitic and ferruginous substrates. We classified the sampled species according to life‐history traits related to species persistence, reproduction, and biological interactions. Functional dissimilarity among plant physiognomies and the two substrate types and the role of soil factors affecting the dissimilarities were assessed. Pollination and seed dispersal syndromes, mycorrhizal association, and reproductive phenology were the main traits defining the PFTs. We found distinct functional structure between plant communities of different substrates and physiognomies, with a marked influence of chemical and physical soil factors. Also, we defined main PFTs profiles for each physiognomy, identifying core PFTs with basic combinations of traits, common to all or almost all physiognomies. The functional perspective proposed by this study provides applicable knowledge to the restoration and conservation of campo rupestre ecosystem, reinforcing the importance of habitat heterogeneity for maintaining its functioning.